Prevalence, socioeconomic factors and obstetric outcomes associated with adolescent motherhood in Ceará, Brazil: a population-based study - Shirley Kelly Bedê Bruno; Hermano Alexandre Lima Rocha; Sabrina Gabriele Maia Oliveira Rocha; David Augusto Batista Sá Araújo; Jocileide Sales Campos; Anamaria Cavalcante e Silva; Luciano Lima Correia (BMC, 2021)
Abstract Background Adolescent motherhood (AM) remains a public health problem, especially in low and middle income countries, where approximately 95% of these births occur. Evidence from studies with population representativeness about events associated with AM is limited. We assessed the prevalence of AM, as well as its association with Socioeconomic Factors and Obstetric Outcomes. Methods A population-based cross-sectional study on maternal and child health of women aged 10 to 49 years, living in the state of Ceará, in northeastern Brazil was carried out to assess the prevalence of AM, as well as its association with Socioeconomic Factors and Obstetric Outcomes. The definition of adolescence used in the study was the one utilized by the WHO. In addition to the interview, data were double-checked according to the information in the government's pregnancy health booklet. Sample-adjusted logistic models to determine the association of socioeconomic factors and AM, as well as the association of AM with obstetric outcomes, with a causal approach to multivariate analyses, were used. Results The prevalence of adolescent motherhood was 18.6%. Poverty and household crowding were associated with greater chances of AM (p values of 0.038 and <  0.001, respectively), as well as not being in a stable relationship (OR 2.26 (95%CI: 1.67, 3.07), p <  0.001). AM showed a greater chance of not using community health services (p <  0.001), had fewer prenatal consultations (β − 0.432 (95%CI: − 0.75, − 0.10)) and started prenatal care at a later date (β 0.38 (95%CI: 0.21, 0.55), p <  0.001)). AM are also less likely to be tested for HIV and more likely to have urinary tract infections. Conclusions Interventions aimed at socially-vulnerable adolescents are suggested. However, if pregnant, adolescents should receive proactive and differentiated prenatal care.